The wind through the keyhole - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2016)
Sent by his father to investigate evidence of a murderous shape shifter, a "skin man," Roland Deschain takes charge of Bill Streeter, a brave but terrified boy who is the sole surviving witness to the beast's most recent slaughter. Roland, himself only a teenager, calms the boy by reciting a story from the Magic Tales of the Eld that his mother used to read to him at bedtime, "The Wind through the Keyhole." The novel can be placed between Dark Tower IV and Dark Tower V.